KEBIJAKAN KURIKULUM MERDEKA UPAYA MENINGKATKAN PENDIDIKAN KARAKTER DI INDONESIA - Teti Rosminda; Fadriati Fadriati (STAI Ma'had Aly Al-Hikam Malang, 2023)
The purpose of this research is to comprehensively discuss educational problems related to the latest curriculum policy, namely the independent curriculum. This curriculum emphasizes educational institutions to strengthen on three very basic aspects, namely independent sharing, independent learning and independent change. Three aspects are the benchmarks in making quality education for each educational institution in Indonesia. The author sees and provides an explanation of the three aspects contained in the independent curriculum. Is that really the answer to the national education system? The independence of each student is shackled from the previous curriculum, because 11 times the educational curriculum has changed in line with the changing policy makers. With the independent learning curriculum policy, it will be able to improve the character of students in educational institutions in Indonesia. The author uses a qualitative research approach and the type of research is literature study. The data collection is collected from various journals, articles and books that are appropriate to the research topic. Sorting the data obtained is described according to the discussion, which includes reducing data, presenting data and drawing conclusions.